Relações entre variáveis ambientais e anfíbios anuros em áreas de cerrado e floresta estacional semidecidual - Maffei, Fábio [UNESP] (2014)
Amphibians are ectothermic and their body temperature is associated with their environment. They depend on aquatic and humid habitats for reproductive success, and diversity is highest in the neotropical region, where the climate is suitable to most species. This close relationship with climate variations is extremely important in areas where seasonality regulates amphibian populations. The Cerrado and Mesophytic Semideciduous Forest of the São Paulo Western Plateau exhibit these characteristics, with two well defined seasons throughout the year, with a hot and rainy summer and a cold and dry winter. In this study, I examined (1) the composition and seasonality of six anuran assemblages in the São Paulo Western Plateau, (2) the similarity of these communities with those of other sites in inland São Paulo state, (3) the influence of climate variables in the calling season of species, and (4) the hypothesis that temperature amplitude influence the richness and abundance of anurans. Between September 2011 and May 2013, six water bodies were sampled in the municipalities of Águas de Santa Bárbara, Agudos, Avaré, Borebi, Lençóis Paulista, and Jaú. Of the 68 species known to occur in the São Paulo Western Plateau, 39 were recorded in the present study. Frog vocalization was seasonal and concentrated in the summer, with higher activity between November and December. Like most species of inland São Paulo state, the community of frogs sampled is typical of open areas with a high plasticity regarding habitat use. Among the environmental variables analyzed, the most important were photoperiod and temperature, including temperature amplitude, which most times was inversely correlated to precipitation and humidity. The correlation of richness as well as abundance in the six areas sampled was highest with photoperiod, followed by temperature. The influence of precipitation, atmospheric pressure, and humidity on species was low, with wind ...